PACD adult education activities in Cagayan - Castillo, Gregoria Ancheta (Gutierrez) 1934- (s.n.], 1967)
This study analyzed how the PACD adult education activities in Cagayan have been implemented by CD workers. The study includes the particular activities that CD workers enjoy most, activities they want to concentrate on, activities they want to engage in, the methods used in carrying out their activities, problems they have met, and their suggestions for a more efficient implementation of their activities. This also determines the reactions of the adults to the activities of the CD workers.